The impact of framing effects, competitive state, and time pressure on risk-taking decisions in tennis players of different skill levels - Shangguan, Rong; Zha, Zihan (Frontiers in Psychology, 2025)
Athletes’ risk decision-making significantly influences competitive performance; however, current research remains controversial regarding how framing effects, competitive state, and time pressure affect risk decisions among athletes of different skill levels. Through two experiments, this study investigated the effects of frame type (positive/negative), competitive state (leading/trailing), and time pressure (high/low) on risk decision-making among tennis players of varying proficiency levels. Both Experiments 1 and 2 recruited 120 tennis players (40 participants each in expert, skilled, and novice groups, with a male-to-female ratio of 3:1). The findings revealed that: (1) The novice group exhibited the highest susceptibility to framing effects, maintaining this characteristic even under high time pressure; (2) the skilled group demonstrated distinctive “transitional characteristics,” showing susceptibility to framing effects without time pressure but shifting toward extremely conservative decisions under high time pressure; (3) the expert group displayed the most stable decision-making patterns, primarily basing decisions on competitive state—adopting conservative strategies when leading and aggressive strategies when trailing, with minimal influence from framing effects and time pressure. The study demonstrates significant differences in risk decision-making characteristics across skill levels: novices possess immature decision-making mechanisms and are readily influenced by emotional and external factors; skilled players are in a developmental phase of decision-making ability, exhibiting notable context dependency; whereas experts demonstrate mature decision-making mechanisms, capable of making stable strategic choices based on competitive state. These findings provide novel theoretical perspectives for understanding the developmental patterns and influencing factors of athletes’ risk decision-making.